Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Menulis Karangan Argumentasi Siswa Kelas IX SMP Muhammadiyah 1 Kota Tangerang - Supyan Sori (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to determine the effect of the problem-based learning model on the ability to write argumentative essays for class IX students of SMP Muhammadiyah 1 Tangerang City. The method used in this study is a quasi-experimental method by conducting a pretest and posttest in two groups. This type of experimental research method uses a nonequivalent control group design, where the experimental class is treated and the control class is not treated. The data collection technique used a test in the form of an essay test in the form of performance in writing an argumentative essay. The data analysis technique starts from the normality test, homogeneity test, and continues to test the hypothesis. The results showed that post-test or final test data were obtained which were then analyzed using a two-party t-test, giving the result that students who were given treatment with problem-based learning models experienced more improvement than students who were not given PBM learning strategies. This can be seen from the calculation results, that the value of tcount > ttable value with the acquisition of tcount of 0.94 while for ttable of 2.0084. This proves that the hypothesis is accepted, namely that there are differences in students' ability to write argumentative essays between students who are given a problem-based learning model and students who are not given a problem-based learning model.